Geriatric evaluation in lung cancer care: a survey of daily practice - Schulkes, Karlijn J; Hamaker, Marije E; Lammers, Jan-Willem J; van Elden, Leontine J (European Journal of Oncology and Environmental Health, 2018)
Background: To identify ways to improve care for older lung cancer patients, we set out to examine how older lung cancer patients in the Netherlands are currently being analysed prior to oncological treatment and to explore the potential obstacles in the incorporation of a routinely performed geriatric evaluation. Methods: We sent a web-based survey to 138 Dutch pulmonologists specialized in lung cancer care between April and September 2015. Results: The response rate was 37%. According to the answers of the responding pulmonologist, a geriatric evaluation was available in 90% of the hospitals. This was performed routinely in a minority of the hospitals (45%) on the basis of age (18%), with use of some form of screening tool (27%), however mostly performed on ad hoc basis (56%). More than half (52%) of the respondents answered to be not, or not completely, satisfied with current geriatric evaluation. The main obstacles for implementing geriatric evaluation in standard care were lack of a structured format for this evaluation and lack of geriatric oncologic expertise. Conclusion: There is interest in the incorporation of a geriatric evaluation in the care for the heterogeneous elderly population with lung cancer. However, at the moment the optimal set-up for geriatric oncologic care is lacking. There seems to be no consensus about the optimal design in terms of patient selection, timing and use of screening tools. A closer collaboration between pulmonologists specialized in lung cancer care and geriatricians could help to improve appropriate care for elderly patients with lung cancer.